Adaptasi Speech Code Komunikasi Antar Budaya Toraja dan Salatiga - Dewi M.K1; Berta Esti Ari Prasetya (STIE AMKOP, 2022)
Indonesia is a multicultural country that provides cultural diversity. This study aims to describe how the form of speech code adaptation and the impact of adapting intercultural communication on Satya Wacana Christian University students from Toraja who migrated to Salatiga. Data collection techniques in this study used observation and interviews. The results of this study indicate that in adjusting the interaction of verbal communication and non-verbal communication goes well. In the speech code adaptation process, the results obtained in the honeymoon phase that students from Toraja felt happy when they were new to the city of Salatiga and were enthusiastic about learning the language style and culture of Salatiga. In the second phase of frustration, the students from Toraja did not experience frustration and chose to adjust the culture and style of language in their new environment. In the readjustment phase, students from Toraja can adapt by understanding and learning all the differences in culture and language styles in Salatiga. In the last stage in the resolution phase, students from Toraja decided to accept the culture and style of language but did not eliminate the culture and style of their original language. Keywords: Culture, Language Style, Speech Code, Speech Code Adaptation